Helical cyclogenesis as an extreme threshold phenomenon in a rotating stratified moist atmosphere - Levina, Galina (Frontiers in Earth Science, 2024)
The concept of helical cyclogenesis is discussed, allowing for a unified interpretation of the existence of intense large-scale long-lived vortices in the atmosphere through the transfer of energy from cloud-scale motions. In 2022, the first evidence of such phenomenon was found at Jovian high latitudes. The theory introduces ideas about large-scale threshold instabilities in turbulence with broken mirror symmetry. Such turbulence, called the helical one, occurs in a rotating, stratified, moist atmosphere. The present publication emphasizes the problem of tropical cyclogenesis in the Earth's atmosphere. In the case of tropical cyclones, these ideas allowed for the first time to develop a procedure for the exact diagnosis of the emergence of large-scale helical-vortex instability and interpret this event as the birth of a tropical cyclone. Our very simple diagnostics and lucid quantitative criterion of the tropical cyclogenesis are discussed in the context of their successful application to two distinct idealized genesis scenarios and three observed tropical cyclones. In all cases, a nascent vortex became energy-self-sustaining and intensifying dozens of hours before the formation of a tropical depression. The pivotal role of rotating cumulonimbus clouds, known as vortical hot towers (VHTs), is highlighted. They are a necessary element both to provide and to diagnose the instability. These main actors of the helical cyclogenesis are illustrated by authors' photos, satellite imagery, and animation from idealized atmospheric modeling. New fundamental and applied interpretations are offered. The hypothesis on the two-scale vortex dynamo-effect is put forward, which suggests the energy transfer from the VHTs scale, 10-30 km, directly to the mesoscales, hundreds km, of the system circulation of a tropical cyclone. Based on the results of application of the new diagnostics, we propose to consider the onset of this new instability as the beginning of the genesis stage while the tropical depression formation as the completion. The diagnostics is best suited as a fundamental basis for detecting to declare the stage "Potential Tropical